Mitosis-specific phosphorylation of PML at T409 regulates spindle checkpoint - Jin, J; Liu, J (Cellular and Molecular Biology, 2016)
During mitosis, Promyelocytic leukemia nuclear bodies (PML NBs) change dramatically in morphology and composition, but little is known about function of PML in mitosis. Here, we show that PML is phosphorylated at T409 (PML p409) in a mitosis-specific manner. More importantly, PML p409 contributes to maintain the duration of pro-metaphase and regulates spindle checkpoint. Deficient PML p409 caused a shortening of pro-metaphase and challenged the nocodazole-triggered mitotic arrest. T409A mutation led to a higher frequency of misaligned chromosomes on metaphase plate, and subsequently death in late mitosis. In addition, inhibition of PML p409 repressed growth of tumor cells, suggesting that PML p409 is a potential target for cancer therapy. Collectively, our study demonstrated an important phosphorylated site of PML, which contributed to explore the role of PML in mitosis.